Perbandingan Kinerja Aerodinamika Berbagai Geometri Bodi terhadap Gaya Hambat dan Gaya Angkat pada Kendaraan Hemat Energi - Reinaldi Teguh Setyawan; Hajar, Ibnu; Gunawan, Gunawan (P3M Politeknik Negeri Jember, 2025)
The geometric shape of a vehicle's body plays a critical role in determining aerodynamic efficiency, particularly in lightweight, energy-efficient vehicles. This study analyzes and compares the aerodynamic performance of three body shapes—boxy, wedge, and streamline—based on mathematical calculations using physical parameters and aerodynamic coefficients sourced from established technical literature. Drag force (????d) and lift force (????l) were calculated using classical aerodynamic formulations, referring to Bernoulli’s principle and standard fluid dynamics equations, at a constant vehicle speed of 60 km/h with frontal area estimations derived from proportional two-dimensional sketches. The results indicate that the streamline body yields the lowest aerodynamic forces, with a drag force of 38.27 N and a lift force of 15.31 N, significantly lower than the boxy shape which generates 64.12 N and 37.10 N, respectively. This demonstrates the effectiveness of streamlined geometry in reducing air resistance and improving vertical stability. In conclusion, theoretical aerodynamic analysis can provide reliable early-stage design insights for energy-efficient vehicles without the need for complex simulations.